Moving Beyond the Link Between HRM and Economic Performance: A Study on the Individual Reactions of HR Managers and Professionals to Sustainable HRM - Guerci, Marco (Journal of business ethics, 2019)
This study contributes to the growing literature on the intersection between human resource management and corporate sustainability (CS) and, in particular, on sustainable human resource management (interpreted here as HRM practices informed by the CS principles, thus aiming at economic, social, environmental and human sustainability simultaneously). In particular, this paper claims that the members of the HR professional community can increase their job satisfaction and decrease their intention to leave by implementing sustainable HRM. In addition, we test for the mediating role played by the meaning that HR professionals and managers attach to HR work. Indeed, when HR professionals and managers are involved in sustainable HRM perceive their job to become more meaningful as it has a broader scope which goes beyond the solely focus on economic performance, and that leads then to higher job satisfaction and lower turnover intention. The study, which is based on 176 questionnaires collected through a cross-country survey, has been developed in partnership between the authors and a leading European association of HR managers and professionals. Our findings, which in general extend the knowledge on the employees’ perception of CS—employee attitudes relationships, represent a data-driven argument for a more active role of HRM in developing Sustainable HRM.